Is it possible for the Judiciary to interfere in any area? (Revista do Tribunal Regional Federal da 3ª Região, 2022)
This article intends to discuss, in the light of historical facts, in the USA and Brazil, the possible limits of the Judiciary's actions.
Keywords: Judiciary; Unconstitutionality; Functional competence; Self-restraint; Reserving the possible